2015
DOI: 10.1002/jcsm.12045
|View full text |Cite
|
Sign up to set email alerts
|

p62/SQSTM1 but not LC3 is accumulated in sarcopenic muscle of mice

Abstract: AimWe investigated the pathway of autophagy signaling linked to sarcopenia of mice.MethodsYoung adult (3‐month) and aged (24‐ month) C57BL/6J mice were used. Using real‐time PCR, Western blotting, and immunohistochemical microscopy, we evaluated the amounts of p62/SQSTM1, LC3, and Beclin‐1 in the quadriceps muscle change with aging in mice.ResultsMarked fiber atrophy (30%) and many fibers with central nuclei were observed in the aged mice. Western blotting using homogenate of the cytosolic fraction clearly sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 46 publications
9
51
1
Order By: Relevance
“…Moreover it has been shown that defective autophagy contributes to the pathogenesis of different forms of muscular distrophies associated with accumulation of altered organelles into myofibers or abnormal degradation of myofibers components 57 . Also ageing is accompanied by autophagic defects as shown by studies performed in human and mice skeletal muscles 58,59 . Overall these evidences support the concept that cisplatin treatment recapitulates the main features of cancer-induced cachexia, and thus making the cisplatin-treated rats an useful and valuable model to investigate the molecular bases of this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover it has been shown that defective autophagy contributes to the pathogenesis of different forms of muscular distrophies associated with accumulation of altered organelles into myofibers or abnormal degradation of myofibers components 57 . Also ageing is accompanied by autophagic defects as shown by studies performed in human and mice skeletal muscles 58,59 . Overall these evidences support the concept that cisplatin treatment recapitulates the main features of cancer-induced cachexia, and thus making the cisplatin-treated rats an useful and valuable model to investigate the molecular bases of this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of p62 generally indicates an impairment of autophagy flux (46), but p62 hyperexpression was also observed in cancer cachexia-induced skeletal muscle atrophy despite the autophagy induction (56). In addition, a recent study reported the accumulation of p62 in atrophic muscle of aged mice (60). Although our findings indicate that AMPK modulates the expression of autophagy-related proteins during unloading-induced muscle atrophy, we cannot ascertain whether AMPK-mediated autophagy regulation is associated with the progress of muscle atrophy in response to hindlimb unloading.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated levels of LC3 and Beclin-1 mRNA expression were also reported in skeletal muscle after 3 or 7 days of denervation [64]. Under such conditions of inactivity, such as the late phase, autophagy seems to modulate muscle atrophy accompanying inactivity [96].…”
Section: Physical Disabilities -Therapeutic Implicationsmentioning
confidence: 75%